Cornual Pregnancy - Wazed, F; Sultana, N; Ahamed, S; Khan, JH; Rouf, S; Mojumder, U (Journal of Medicine, 2012)
Cornual pregnancy is rare form of ectopic pregnancy where implantation occurs in the cavity of a rudimentary horn of the uterus. It is the diagnostic and therapeutic challenge with potential sever consequence if uterine rupture occurs with massive intra abdominal haemorrhage .We report a case of misdiagnosed rupture cornual pregnancy occurring at 12 weeks gestation. First USG revealed intra uterine pregnancy. Repeat USG showed abdominal pregnancy sac but cornual pregnancy was not diagnosed and uterine anomaly was not detected. The correct diagnosis was made at emergency laparotomy. An intact pregnancy sac of 12weeks fetus was seen in abdominal cavity. Placenta and pregnancy sac was adherent to omentum and torn end of left cornu of the bicornuate uterus. Left sided cornu was resected keeping both the ovaries and tubes intact. DOI: http://dx.doi.org/10.3329/jom.v13i2.12763 J Medicine 2012; 13 : 227-229